Detoxification of Gadung (Dioscorea hispida Dennst.) by Mucor sp. Fermentation - Sasongko, Pramono (Jurnal Teknologi Pertanian, 2009)
Dioscorea hispida Dennst. or gadung-yam is one of the tuber crops in Indonesia. Nevertheless, people are still unaware to consume gadung-yam and its derivative product, because of toxic compounds such as alkaloid and cyanide. Therefore, it is necessary to have a detoxification process to decrease the concentration of cyanide to have safe product of gadung-yam such as gadung flour. A detoxification can be carried out by a fermentation method, which accelerates the breakdown of cyanides. The fermentation will produce more volatile HCN in gadung flour which evaporate in drying process. The fermentation in this research used Mucor sp. The objective of this research was to obtain the optimum concentration of Mucor sp. and the the fermentation time to produce less cyanide gadung flour. The experimental design of the research was Factorial Randomized Block Design with two factors. The first factor was the concentration of mold with four levels, i.e. 0%, 5%, 10%, and 15%. The second factor was the fermentation time with 3 levels i.e. 24, 48 and 72 jam. The data was analyzed using anova followed by LSD or DMRT test with ï¡ = 0.05.The results showed that there was significant interaction between the mold concentration and the fermentation time on starch, reducing sugar, total sugar, and fiber content. Â However, there was no significant interaction between treatments on moisture and cyanide content. The best treatment was the combination of 5% mold and 72 hours fermentation. Â The characteristic of this gadung-flour were 4.01% of moisture content, 21.74 ppm of cyanide content; 46.66% of starch content; 3.6% of fiber content; 17.00% of total sugar content; 9.52% reducing sugar content; L* colour of 60.97; a* of 13.27; b* of 18.45; Â 3.27% of higroscopicity, and starch gelatinization temperature of 83ÂºC.Keywords: gadung, detoxification, yams flour, fermentation, Mucor sp.